2017
DOI: 10.1016/j.ijproman.2017.01.006
|View full text |Cite
|
Sign up to set email alerts
|

Benefit sharing for BIM implementation: Tackling the moral hazard dilemma in inter-firm cooperation

Abstract: Building information modelling (BIM) plays an important role in furthering value-creation of construction projects by advocating the inter-firm cooperation. When implementing BIM, however, individual firms inherently safeguard their self-interests regardless of the fact that inter-firm cooperation might reap joint BIM benefits for a project overall, which epitomizes a typical problem of moral hazards in project-based organizations. This paper develops an outcome-linked benefit sharing model that considers shar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
47
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(48 citation statements)
references
References 31 publications
1
47
0
Order By: Relevance
“…Our finding that BIM is causing fewer unplanned changes corresponds to the findings by Barlish and Sullivan [7], McGraw Hill Construction [2], and Ghaffarainhoseini et al [28]. Similar to other studies [2,30,33], our research also indicated that BIM use results in less rework.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Our finding that BIM is causing fewer unplanned changes corresponds to the findings by Barlish and Sullivan [7], McGraw Hill Construction [2], and Ghaffarainhoseini et al [28]. Similar to other studies [2,30,33], our research also indicated that BIM use results in less rework.…”
Section: Discussionsupporting
confidence: 91%
“…Benefits of using BIM are shared among the project participants; for example, benefits experienced by the design team could include less rework and fewer RFIs which provide benefits for the contractors in the construction phase as well as overall benefits to the client. As BIM benefits can be shared among clients, designers, and contractors, stakeholders are not exposed to loss during this collaboration, and, therefore, they are more motivated to implement BIM on projects [30]. Another example of BIM benefits experienced by multiple stakeholders is a location-based design process that helps design team minimize waste of time spent on building information modeling [31].…”
Section: Stakeholder Perceptions Of the Benefits Of Bimmentioning
confidence: 99%
See 2 more Smart Citations
“…As a result, participants are very likely not to cooperate sincerely, and only provide conceptual BIM-based product to the owner. This is a severe problem that existed in IPD-based organizations, which is known as a moral hazard dilemma that is adverse to the overall project performance in the AEC industry [21].…”
mentioning
confidence: 99%